2021
DOI: 10.3390/land10060644
|View full text |Cite
|
Sign up to set email alerts
|

Urban Land Use Transitions and the Economic Spatial Spillovers of Central Cities in China’s Urban Agglomerations

Abstract: Urbanization and land use transformation are typical characteristics of China in recent decades. Studying the effects of urban land use transitions (ULUT) on the economic spatial spillovers of central cities (ESSCC) can provide a reference for China to optimize cities’ land space layout and promote their coordinated development. Based on the direct and indirect effects of ULUT in central cities on the production factors and economic growth in other cities, this paper reveals the mechanisms underlying the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Based on the basic characteristics of agricultural land, the law of diminishing returns of land shows that the input and output of land do not always have a positive relationship, and, for parcels in different spatial locations in cities, the degree of intensive use does not increase with the increase in the input of productive resources [43]. For a parcel of land, there are many factors that characterize intensive use, such as the comprehensive floor area ratio, the building density, the occupancy rate of commercial properties, the degree of functional compatibility between the use of the land and surrounding parcels, and the diversity of commercial uses.…”
Section: Parcel-based Index System For Evaluation Of the Intensificat...mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the basic characteristics of agricultural land, the law of diminishing returns of land shows that the input and output of land do not always have a positive relationship, and, for parcels in different spatial locations in cities, the degree of intensive use does not increase with the increase in the input of productive resources [43]. For a parcel of land, there are many factors that characterize intensive use, such as the comprehensive floor area ratio, the building density, the occupancy rate of commercial properties, the degree of functional compatibility between the use of the land and surrounding parcels, and the diversity of commercial uses.…”
Section: Parcel-based Index System For Evaluation Of the Intensificat...mentioning
confidence: 99%
“…The issue of the intensification of land use in cities is a central topic in urban research and management [43][44][45]. In recent years, commercial land use has gradually become the focus in evaluating land-intensive uses in cities [21].…”
Section: Introductionmentioning
confidence: 99%
“…As this "bottom-to-bottom" competition becomes increasingly fierce, the sale of industrial land gradually evolves from the appropriately low price typically found at the beginning, to the "loss" sale price [10,11]. This directly leads to the distortion of China's industrial land prices and has a far-reaching impact on the sustainable land use [12,13]. Low land prices reduce enterprises' cost of entry to a large extent; low prices therefore become an effective behavior engaged in by local governments to attract enterprises [14,15].…”
Section: Industrial Land Price Distortion and Enterprise Entrymentioning
confidence: 99%
“…This phenomenon is especially common in developing countries [7][8][9]. An important direction for optimizing the rural human-land relationship and regional system functions is to revitalize rural land elements, activate "sleeping" assets, improve rural land use efficiency while ensuring rural revitalization industry land needs, and take land as the core to drive the integration and reconstruction of rural population, capital and technical elements [10][11][12][13]. In the context of the strictest cultivated land protection and the Land 2022, 11, 379. https://doi.org/10.3390/land11030379 https://www.mdpi.com/journal/land prudent promotion of the reformation of the homestead system, the innovative use of rural collective construction land is particularly critical.…”
Section: Introductionmentioning
confidence: 99%